Construção de cidades saudáveis e o agronegócio: desafios e perspectivas de Sorriso (MT) - Benachio, Marcus Vinicios (2018)
The present research fosters a transversal reading of the Municipality of Sorriso (MT), facing the elements that make up quality of life. We understand that the expressions Cities and Healthful Municipalities are dialectical pairs and, multiple strategies supported by our methodology help our work route, as well as documentary and field research, since the qualitative research is made present in our tracing of focus, concepts of healthful and sustainable cities, definitions of public policies and urban evolution are illustrated by the theoretical benchmark. This study contemplates subjective human relations in space and territory, the cultural, political and physical conditions permeate our epistemological analysis, strengthening questions about the arrangements that cities shape for the quality of life. The choice of Sorriso (MT) occurs due to its regional peculiarity, occupying the area of the Legal Amazon, and also responds as the capital of the National Agrobusiness. Its accelerated growth and versatile economy can sustain new systems for living. In order to interpret quality of life, we seek the World Health Organization (WHO), which provides indicators for the development of a municipality, which is based on: promoting greater information in the areas of health, services, democratic management (with greater popular participation) , of works, of transport, of work, of leisure, education, among other fundamental subsidies for social progress. We can consider that Sorriso (MT) is far from being a healthful municipality, since its mode of urban structuring is still frozen in time, fueled by short-term capitalist projects and ideas.